Exploring determinants of breeding success in the Greenland Barnacle Goose Branta leucopsis - Redmond, Courtney; Cabot, David; Doyle, Susan; McMahon, Barry J. (Wildfowl, 2023)
In many bird species across a variety of taxa, larger individuals with greater body stores are more likely to breed successfully. The migratory Barnacle Goose Branta leucopsis breeds in arctic regions including Greenland, Svalbard, Russia, and the North and Baltic Seas. Larger body size and metabolic body stores (weight relative to body size) have been linked to increased fitness through larger clutch size, social dominance, better overall health and more efficient feeding for the Svalbard and Baltic subpopulations, but this has not yet been shown for the Greenland subpopulation. In Greenland, the geese breed in remote areas inaccessible for study, but observations made on the wintering grounds in northwest Scotland and Ireland can provide important insight into factors affecting trends in abundance. To determine the influence of larger body stores or physical size on breeding success in the Greenland Barnacle Goose subpopulation, a dataset with 60 years of morphometric measurements and field observations at one of the principal wintering grounds in Ireland was analysed. Both males and females with larger body stores were more likely to breed successfully, and this relationship was significant. Males with larger body size were also more likely to breed successfully, although this relationship was not significant. Similar relationships were not seen with pairing success, suggesting that body stores and size may have more direct influence on the ability to raise offspring than on securing a mate. While all of the Barnacle Goose subpopulations showed a dramatic increase in the past 60 years, they are susceptible to pressures on both breeding and wintering grounds (e.g. human–wildlife conflicts and avian influenza), necessitating an understanding of the factors that contribute to their population dynamics.